Characterization of the intestinal microbiota in snook (Centropomus sp.) and isolation of potential probiotic bacteria - Zatán Valdiviezo, Adrian Edú (2020)
The aim of this study was to characterize the microbiota of the intestinal tract of robalo (Centropomus sp), from natural environment and captivity, and to isolate and identify bacteria with probiotic potential. The intestinal microbiota was characterized by metagenomics directed to the 16S rRNA gene. In addition, samples of intestinal mucus were cultured in MRS medium for bacterial isolation. Molecular identification was done by sequencing the 16S rRNA gene. Probiotic capabilities were evidenced by proteolytic and bacterial antagonism assays against Plesiomona shigelloides, Aeromonas hydrophila, Aeromonas veronii and Vibrio harveyi. The most abundant bacterial genera were Clostridium, Photobacterium, Cetobacterium and Rubritepida. Bacterial species, including Klebsiella sp, two strains of Weisiella cibaria and Lactococcus sp were isolated on MRS agar from the intestinal tract. W. cibaria strains showed broad antagonistic spectrum and positive proteolytic activity.